Altered Spontaneous Brain Activity Patterns of Meibomian Gland Dysfunction in Severely Obese Population Measured Using the Fractional Amplitude of Low-Frequency Fluctuations - Xu, Yu-Ling; Wang, Xiao-Yu; Chen, Jun; Kang, Min; Wang, Yi-Xin; Zhang, Li-Juan; Shu, Hui-Ye; Liao, Xu-Lin; Zou, Jie; Wei, Hong; Ling, Qian; Shao, Yi (Frontiers in Psychiatry, 2022)
Objective: Utilizing the fractional amplitude of low-frequency fluctuations (fALFF) technique, this study sought to correlate spontaneous cerebral abnormalities with the clinical manifestations of meibomian gland dysfunction (MGD) in severely obese (SO) population. Subjects and Methods: Twelve MGD patients in SO population (PATs) (4 males and 8 females) and twelve healthy controls (HCs) (6 males and 6 females) matched by gender and age were enrolled. Every participant underwent resting-state functional magnetic resonance imaging (rs-MRI) scanning. Spontaneous cerebral activity alterations were examined using the fALFF method. Receiver operating characteristic (ROC) curves were utilized to classify the medial fALFF values of the PATs and HCs. PATs were also asked to complete anxiety and depression score forms, permitting a correlation analysis. Results: In contrast with HCs, PATs had prominently increased fALFF values in the left lingual gyrus, the right globus pallidus, the right anterior cingulate and paracingulate gyri and the left middle occipital lobe (P<0.05), and decreased fALFF values in the right cerebellum, the left fusiform gyrus, the right medial orbitofrontal gyrus, the left triangle inferior frontal gyrus and the left inferior parietal gyrus (P<0.05). The results of the ROC curve indicated that changes in regional fALFF values might help diagnose MGD in SO population. Moreover, fALFF values in the right cerebellum of PATs were positively correlated with hospital anxiety and depression scores (HADS) (r=0.723, P=0.008). The fALFF values in the left triangle inferior frontal gyrus of PAT were negatively correlated with HADS (r=-0.651, P=0.022). Conclusions: Aberrant spontaneous activity was observed in multiple regions of the cerebrum, offering helpful information about the pathology of MGD in SO population. Aberrant fALFF values in these regions likely relates to the latent pathologic mechanisms of anomalous cerebral activities in PATs.